Bibliometric Study: Effectiveness of Physics Learning Media in The Merdeka Belajar Curriculumto Improve Students’ Critical Thinking Skills - Afaurina Indriana Safitri; Setyo Admoko (Postgraduate, University of Mataram, 2024)
This research aims to determine the effectiveness of physics learning media in the Merdeka Belajarcurriculum in improving students' critical thinking abilities. The article writing method is through literature study by integrating the PRISMA stages in it. The process of searching for relevant article sources was carried out using Publish or Perish software in the 2022-2023 interval. The metadata obtained was then analyzed using VOSviewer software to obtain a qualitative descriptive bibliometric meta-analysis. The results of the qualitative bibliometric analysis show that the physics learning media (PhET simulations, quiz platforms, MOOCs, videos, YouTube content, Adobe Animate) in the Merdeka Belajar curriculum is proven to be effective in improving students' critical thinking abilities. Apart from that, this research has been updated in the form of new ideas in bibliometric analysis on topics related to the Merdeka Belajar curriculum. The impact of this research is that it can provide updates in the world of research related to research on topics that revolve around the Independent Curriculum. This is certainly able to enrich references for future progress in the world of education, especially in the use of types of learning media that are appropriate to the curriculum used.